DNA array image analysis : (DNA Press, 2002)
All DNA and protein array-based technologies require the analysis of digital images of the scanned DNA array, however the study of microarray image processing is often neglected. The editors of this title believe this is an important omission as the quality and consistency of the image analysis is vital for accurate experimentation. This title focuses on the theoretical and practical considerations of image analysis, guiding the readers through the various technologies available and offering practical tips for both the novice in the field and the advanced user.